Development and applicability of heat transfer analytical model for coaxial-type deep-buried pipes. (15th September 2022) - Li, Chao; Jiang, Chao; Guan, Yanling; Tan, Zijing; Zhao, Zhiqiang; Zhou, Yang
Abstract: Based on the infinite line source model and logarithmic mean temperature difference, an analytical model for solving the heat transfer of coaxial-type deep-buried pipe has been proposed in this investigation. The actual assignment of vertical lithology and temperature values of the ground around the buried pipes could be realized by layered modeling. To validate the analytical model in terms of reliably calculating the real-time and on-way water temperature of buried pipes, the field experiment of buried-pipe heat transfer (at a depth of 2539 m in Xi'an) was carried out, and the numerical model developed based on the experiment was employed for corroboration. Further, by setting combined conditions of multiple factors affecting the heat transfer of buried pipes, the applicability of the analytical model under different model parameter combinations was substantiated, and the main factors affecting the calculation accuracy of the analytical model were analyzed. The results showed that the relative error between the analytical solution and experimental value was less than 5.92% for the buried-pipe heat transfer intensity under the experimental condition. The relative error between the analytical and numerical solutions was less than 6.20% under the combined conditions of multiple factors. Highlights: Field heat transfer experiment of coaxial-type deep-buried pipe was carried out. Analytical model of coaxial-type deep-buried pipe heat transfer was developed. The analytical model considered multiple factors affecting buried pipe heat transfer. Analytical model's rationality was confirmed by experimental and numerical methods.